FIGO position statement on postpartum intrauterine devices (PPIUD) - Makins, Anita; Ahsan, Azra; Waqas, Marium; Kasliwal, Asha; Kasliwal, Asha; Ahsan, Azra; Sridhar, Aparna; González, Cuauhtemoc C.; Lam, Wai‐cheung; Bonsergent, Silvia; Momat, Felix; Kallner, Helena K.; et al. (International journal of gynecology and obstetrics, 2025)
Postpartum contraception is a critical intervention to address the unmet need for family planning, which affects over 218 million women globally, predominantly in low‐ and middle‐income countries (LMICs). Immediate postpartum family planning (PPFP) offers a unique opportunity to provide contraception during a crucial health‐seeking encounter, particularly given the rise in institutional births worldwide. Short inter‐pregnancy intervals are associated with increased maternal and neonatal morbidity and mortality, making timely postpartum contraception essential. The postpartum intrauterine device (PPIUD), a long‐acting reversible contraceptive (LARC), is a highly cost‐effective, non‐hormonal method with a low failure rate. It can be safely inserted immediately after vaginal or cesarean delivery, offering women a reliable and accessible option. However, successful implementation of PPIUD services requires overcoming barriers such as fragmented health services, provider bias, sociocultural misconceptions, and supply chain challenges. FIGO advocates for integrating PPFP, including PPIUD, into routine maternity care and emphasizes task sharing, community engagement, and comprehensive counseling as critical strategies. By incorporating postpartum contraception into standard maternal care, particularly in LMICs, health systems can improve maternal and child health outcomes, advance Sustainable Development Goals (SDGs), and empower women to make informed reproductive choices.